Theoretical and Experimental Study of the Intake Manifold Effect on the SI Engine Performance - Rishack, Qais A.; Dakhil, Sadoun F.; Obaid, Mohammed K. (Basrah Journal for Engineering Sciences, 2014)
This work uses different shapes of intake manifold for study the effect on a single cylinder four stroke gasoline engine. A numerical simulation of the flow achieved through five intake manifold designs, using 3D Computational Fluid Dynamic (CFD) software package FLUINT (6.3.). Accordingly, the three-dimensional resolution of Navier-Stokes equations in conjunction with the standard k-ε turbulence model is undertaken to provide knowledge of the air movement nature and examining the intake manifold optimal geometry. Five cases of intake manifold are examined experimentally in order to produce a comprehensive and realistic data set. These data are in the form of engine performance, exhaust gas products and relative AFR for each case separately under different engine speeds. Exhaust gas analyzer type (Infragas-209) is used in the present work to measure exhaust gas concentrations and relative air/fuel ratio ( ). The results were obtained in this investigation showed that a Simulate numerically and experimentally is capable to select the optimized intake system geometry with reliability. Velocity is highest near the outer wall at increased the curvature ratio and pressure is highest near the inner wall at increased the curvature ratio. The secondary flow increases when the engine speeds and curvature ratio increase because of increasing the pressure difference between the inner wall and the outer wall. The effect of these parameters explained on the swirl air movement and tumble inside the cylinder are increasing by increase the engine speed and γ respectively. The increasing in the engine speed and the optimum selection of the manifold which designed enhanced the mixing of the fuel with air. The results showed that the optimized manifold 135º- NE (case 5) due to enhance AFR, fuel consumption and exhaust emissions are improved.